Komunikasi Efektif Kepala Madrasah Ibtidaiyah (MI) Chairiyah Mansuriyah Jakarta Dalam Aspek Manajemen Pendidikan - Keriyono; Rawit Sartika; Sultan Himawan; Faris Saputra Dewa (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The description of the communication structure in school organizations and the role of communication in educational management is one of the research objectives that the author discusses in this study. Literature review in the form of theories that are often used by predecessors which are then studied and reviewed to obtain a concept so that the results are objective. Formal communication, non-formal communication, informal communication, technical communication and procedural communication are forms of communication structures in school organizations that are the results of the study. The communication structure in school organizations is: horizontal communication, diagonal communication, downward communication, and upward communication. In educational management, the role of communication is as a source of educational information, controller and planner and achievement of goals. Communication is also an attempt to increase motivation.